UPLC-MS/MS analysis of antibiotics in pharmaceutical effluent in Tunisia: ecotoxicological impact and multi-resistant bacteria dissemination - Tahrani, Leyla; Mehri, Ines; Reyns, Tim; Anthonissen, Roel; Verschaeve, Luc; Khalifa, Anis Bel Haj; Loco, Joris Van; Abdenaceur, Hassen; Mansour, Hedi Ben (Archives of microbiology, 2018)
The UPLC MS/MS analysis showed the presence of the two antibiotics in the pharmaceutical industry discharges during 3 months; norfloxacin and spiramycin which were quantified with the mean concentrations of 226.7 and 84.2 ng mL −1 , respectively. Sixteen resistant isolates were obtained from the pharmaceutical effluent and identified by sequencing. These isolates belong to different genera, namely Citrobacter, Acinetobacter, Pseudomonas, Delftia, Shewanella , and Rheinheimera . The antibiotic resistance phenotypes of these isolates were determined (27 tested antibiotics-discs). All the studied isolates were found resistant to amoxicillin and gentamicin, and 83.33% of isolates were resistant to ciprofloxacin. Multiple antibiotic resistances were revealed against β-lactams, quinolones, and aminoglycosides families. Our overall results suggest that the obtained bacterial isolates may constitute potential candidates for bioremediation and can be useful for biotechnological applications. Genotoxic effects were assessed by a battery of biotests; the pharmaceutical wastewater was genotoxic according to the bacterial Vitotox test and micronuclei test. Genotoxicity was also evaluated by the comet test; the tail DNA damages reached 38 and 22% for concentrated sample (10×) and non-concentrated sample (1×), respectively. However, the histological sections of kidney and liver’s mice treated by pharmaceutical effluent showed normal histology and no visible structural effects or alterations as cytolysis, edema, or ulcerative necrosis were observed. Residual antibiotics can reach water environment through wastewater and provoke dissemination of the antibiotics resistance and induce genotoxic effects.